Hepadnaviral Lymphotropism and Its Relevance to HBV Persistence and Pathogenesis - Coffin, Carla S.; Mulrooney-Cousins, Patricia M.; Michalak, Tomasz I. (Frontiers in Microbiology, 2021)
Since the discovery of hepatitis B virus (HBV) over five decades ago, there have been many independent studies showing presence of HBV genomes in cells of the immune system. However, the nature of HBV lymphotropism and its significance with respect to HBV biology, persistence and the pathogenesis of liver and extrahepatic disorders remains underappreciated. This is in contrast to studies of other viral pathogens in which the capability to infect immune cells is an area of active investigation. Indeed, in some viral infections, lymphotropism may be essential, and even a primary mechanism of viral persistence, and a major contributor to disease pathogenesis. Nevertheless, there are advances in understanding of HBV lymphotropism in recent years due to cumulative evidence showing that: (i) lymphoid cells are a reservoir of replicating HBV, (ii) are a site of HBV-host DNA integration and (iii) virus genomic diversification leading to pathogenic variants, and (iv) they play a role in HBV resistance to antiviral therapy and (v) likely contribute to reactivation of hepatitis B. Further support for HBV lymphotropic nature is provided by studies in a model infection with the closely related woodchuck hepatitis virus (WHV) naturally infecting susceptible marmots. This animal model faithfully reproduces many aspects of HBV biology, including its replication scheme, tissue tropism, and induction of both symptomatic and silent infections, immunological processes accompanying infection, and progressing liver disease culminating in hepatocellular carcinoma. The most robust evidence came from WHV ability to establish persistent infection of the immune system that may not engage the liver when small quantities of virus are experimentally administered or naturally transmitted into virus-naïve animals. Although the concept of HBV lymphotropism is not new, it remains controversial and not accepted by mainstream HBV researchers. This review summarizes research advances on HBV and hepadnaviral lymphotropism including the role of immune cells infection in viral persistence and the pathogenesis HBV-induced liver and extrahepatic diseases. Finally, we discuss the role of immune cells in HBV diagnosis and assessment of antiviral therapy efficacy.